2020
DOI: 10.1371/journal.pone.0239832
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical comparison of standing posture and during trot between German shepherd and Labrador retriever dogs

Abstract: It is widely accepted that canine breeds stand and move differently. The prevalence of various musculoskeletal disorders such as hip and elbow dysplasia is also different between breeds. German shepherd dog (GSD) and Labrador retriever dog (LRD) are two large breeds with different conformations that have high prevalence of these disorders. This study quantifies the movement and standing posture of twelve healthy GSDs and twelve healthy LRDs to identify biomechanical similarities and differences that may be lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Static weight bearing was, on average, 15.6% of the total body weight on the FHO limb versus 20.3% on the contralateral limb, which sums close to the 37.5% reported to be a normal front/hind body weight distribution ratio in dogs [25], with breed variations from 31% to 38% [26]. This indicates that the dogs are mainly offloading weight to the contralateral hind limb, and not so much to the front limbs.…”
Section: Discussionsupporting
confidence: 68%
“…Static weight bearing was, on average, 15.6% of the total body weight on the FHO limb versus 20.3% on the contralateral limb, which sums close to the 37.5% reported to be a normal front/hind body weight distribution ratio in dogs [25], with breed variations from 31% to 38% [26]. This indicates that the dogs are mainly offloading weight to the contralateral hind limb, and not so much to the front limbs.…”
Section: Discussionsupporting
confidence: 68%
“…Even within the Border Collie breed there is variability in conformation, with differences in shoulder angulation, length of back and loin, and rear limb angulation being notable. Variability of conformation has been shown to affect movement within breeds ( 24 ). This effect may be even greater when performing highly physical activities such as agility, compared with walking and trotting.…”
Section: Discussionmentioning
confidence: 99%
“…Only sex was shown to be a significant factor altering that ratio, with females being below the mean value throughout different breeds [94]. Another study comparing kinematic and kinetic data of orthopedic healthy Labrador retrievers and German shepherds reported that Labrador retrievers carry a higher percentage of the weight on their forelimbs compared to the German shepherd (69% vs. 62%, p < 0.001) [66]. If this breed specific mechanical overload plays a role in the pathogenesis of DED and contributes to the high rate of Labrador retrievers with developmental elbow disease, in particular MCD, is not known.…”
Section: Joint Contact Areas and Force Distribution Within The Elbow Jointmentioning
confidence: 98%
“…The ratio between swing and stance phase depends from the gait pattern and the dog's velocity [28,29,70,71]. At the walk the swing phase of the forelimb accounts for 39 to 43% of the whole gait cycle [60] and increases to approximately 50% to two thirds of the whole gait cycle during the trot, depending from the trotting speed [28,43,45,58,62,64,66]. During running the swing phase is further prolonged and accounts for approximately 75% of the gait cycle [62].…”
Section: The Healthy Elbow Jointmentioning
confidence: 99%
See 1 more Smart Citation